TEKNIK PERIWAYATAN HADIS: PENGERTIAN, BENTUK PERIWAYATAN, SYARAT DAN METODE PERIWAYATAN - virgiawan, luthfi (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The technique of hadith transmission is an important step in ensuring the authenticity ofIslamic teachings, which includes the process of Tahammul (receiving) and Ada’ (delivering)hadith from a teacher to his students. The purpose of this study is to explain the meaning,forms, requirements, and methods of hadith transmission in order to understand themechanism of hadith transmission in the Islamic scientific tradition. The method used is aqualitative method with a type of library study with secondary data sources obtained fromvarious literature, scientific journals, and hadith books recognized in the Islamic tradition.The data collection technique is carried out through a review of literature related to aspectsof hadith transmission, while the data analysis technique uses the Miles and Hubermanmodel, which includes data reduction, data presentation, and drawing conclusions. Theresults of the study indicate that hadith transmission is a process of interaction betweenteachers (sheikhs) and students in the form of tahammul and ada’, with two main forms,namely lafzi and maknawi narration. The valid conditions for hadith transmission are stillrecognized even if its acceptance occurs in a state that does not meet the requirements, aslong as the delivery is carried out after the requirements are met. The methods of narrationinclude eight ways, namely as-sima', al-qira'ah or al-'ardh, al-ijazah, al-munawalah, alkitabah, al-i'lam, al-washiyyah, and al-wijadah.